The Effect of The Gamal Leaf Ethanol Extract on The Growth of Escherichia coli Isolated from Semi Natural Sea Turtle Nest in Boom Beach, Banyuwangi - Hutahaean, Ryan David Pandapotan; Meles, Dewa Ketut; Praja, Ratih Novita; Rahmahani, Jola; Wibawati, Prima Ayu (Jurnal Medik Veteriner, 2022)
The aim of this study was to identify the antibacterial activity potention of gamal leaf (Gliricidia sepium) ethanol extract against Escherichia coli growth which isolated from Olive Ridley Sea Turtle (Lepidochelys olivacea) semi-natural nest in Boom beach, Banyuwangi. The antibacterial test used disk diffusion method. Oxytetracycline 30 µg (Oxoid CT0041B) was used as the Positive Control (K+). CMC Na 0,5% was used as the Negative Control (K-). The treatment (P1, P2, P3, P4) used various concentrations of gamal leaves ethanol extract, which is 40%, 50%, 60%, and 70%. The study assigned six treatments and four replication. The obtained data were analyzed by ANOVA, then continued with the DUNCAN test if the results showed significant differences (p<0,05). The inhibition result of positive control (K+) was 24,70c ± 7.04; and the negative control was 0,00a ± 0,00. All extract concentration result different inhibition, concentration 1 (P1) was 10,41 b ± 3,10; concentration 2 (P2) 8,14 b ± 0,45; concentration 3 (P3) 8,08 b ± 0,47; and concentration 4 (P4) 8,01b ± 0,29. These results indicated that the gamal leaves ethanol extract has antibacterial activity to inhibit the growth of E. coli isolated from Olive Ridley semi-natural nest in Boom beach, Banyuwangi.